THE INFLUENCE OF COMMUNITY PARTICIPATION, TRANSPARENCY IN VILLAGE FUND MANAGEMENT, AND DIGITAL COMPETENCE OF VILLAGE OFFICIALS ON THE EFFECTIVENESS OF VILLAGE FUND UTILIZATION, WITH THE ROLE OF VILLAGE FACILITATORS AS A MEDIATING VARIABLE - Alvi Rachmawati; Sandy Arief (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of community participation, transparency in village fund management, and the digital competence of village officials on the effectiveness of village fund utilization, with village facilitators as a mediating variable. This study is motivated by the suboptimal effectiveness of village fund management and the inconsistent findings of previous studies, particularly regarding the factors influencing effectiveness and the limited examination of the role of village facilitators.This study employs a quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The sample consists of 128 village officials from Bae District, Kudus Regency, selected using a saturated sampling technique. The results indicate that community participation, transparency in village fund management, and the digital competence of village officials have a positive effect on the effectiveness of village fund utilization. These variables also positively influence the role of village facilitators. Furthermore, the role of village facilitators has a positive effect on the effectiveness of village fund utilization and acts as a mediator in the relationship between community participation, transparency, digital competence, and the effectiveness of village fund utilization. The findings suggest that the effectiveness of village fund management is not only determined by internal factors but is also strengthened by the role of village facilitators. This study provides practical implications for village governments in improving the quality of village fund management through enhancing community participation, transparency, and the digital competence of village officials.